541 First aid in the workplace in the world: a systematic review. (24th April 2018) - Dagrenat, Céline; Cassan, Pascal; Issard, Diane; Loeb, Thomas; Baer, Michel; Descatha, Alexis
Abstract : Introduction: Implementing an effective First Aid system at the workplace is a major challenge taking into account the increasing frequency of cardiovascular disorders, easy access of defibrillators, and legal consequences of injury occurring in this particular setting. The aim of the study was to perform a systematic review to evaluate the current knowledge of First Aid techniques at the workplace. Methods: Five databases (Pub-Med, Web of Science, Science Direct, Institut National de recherche et de Sécurité (INRS) and European Reference Centre for First Aid Education (ERCFAE) were searched since 2000, using the keywords « First aid », (« Workplace », or « Occupational disease »). The full-text articles included had to take place at the workplace and to describe a First Aid intervention. A two-stage process with two independent readers was used to select relevant papers. Results: 18 studies were included in the systematic review on the 168 records screened. Studies were mainly from Europe and North America: 5 referred to the regulation of first aid at the workplace, 8 to the organisation, 3 to the training and 2 both to regulation and organisation. Legislation and organisation of the emergencies at the workplace were very different between countries and disparities even existed within a same country. Employees involved in First Aid interventions should benefit from an adequate theoretical and practical training as well as suitable places with an access to the adapted equipment they need. On the training aspect, interest of refresher courses has shown better results in terms of knowledge and theoretical and practical skills. Conclusion: First aid at the workplace seems to be important even if the countries didn't make specific and homogeneous recommendations on the subject. Develop an effective First Aid system at the workplace means acting on occupational injuries and helping to prevent occupational risks.